(untitled) (Fiep Bulletin - online, 2015)
Over the years, football has undergone several changes in their training, both in the tactical, technical and physical side, however things do not change, despite the evolution of the sport. Football is a sport that has many preconceptions, because even with the evolution of professional sports still use old methods that have made him successful in the past, but will not necessarily have the same result in this. Height, for example, has always been a factor that caused discussion in the middle of football, for many it is essential that the athlete is tall to play a specific sport position, causing many promising athletes leave the sport in the basic categories because they not possess such an attribute. The present study sought to investigate whether the height was a key factor for the success of both the athletes and their teams, so ten teams were used for research teams that competed in the Brazilian League Serie A between 2003 and 2013 identified the average height at five positions (goalkeeper, side, defenders, midfielders and attackers). These ten teams were divided into two blocks, the block of success (five teams more often qualified for the Libertadores Cup for the Brazilian League) and the block of failure (five teams more often relegated from the Brazilian League Serie A for the Brazilian League Serie B). Data were collected in the internet, site www.ogol.com.br and thrown into a spreadsheet for analysis. With all the data collected it was found that there was a standard height in all positions with very little variation between one and another and between one block and another. It is concluded that stature analyzed in isolation should not exclude athletes already in the youth, as the results showed that height is not directly linked to success and can see that for several years the stature of the failure block is greater than the block of success.